2020
DOI: 10.3390/f11070775
|View full text |Cite
|
Sign up to set email alerts
|

IoT Monitoring of Urban Tree Ecosystem Services: Possibilities and Challenges

Abstract: Urban green infrastructure plays an increasingly significant role in sustainable urban development planning as it provides important regulating and cultural ecosystem services. Monitoring of such dynamic and complex systems requires technological solutions which provide easy data collection, processing, and utilization at affordable costs. To meet these challenges a pilot study was conducted using a network of wireless, low cost, and multiparameter monitoring devices, which operate using Internet of Things (Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 115 publications
0
25
0
2
Order By: Relevance
“…These elements fulfill most of the formal requirements to recognize an intervention as NBS proposed by Sowi ńska-Świerkosz and García [7] (Table 3). Previous research conducted by other authors in relation to different elements of GBI, including UPs [21,37,38], UFs [40][41][42], UWs [42][43][44][45]52], AGs [16,[46][47][48], and Ws [11,49,50], showed that these elements provide and/or improve environmental, social, and economic benefits, such as recreational and spiritual or cultural ecosystem services, physical and mental health, carbon sequestration, air purification, noise reduction, biodiversity and, in the case of AGs and UWs, food provisioning. In addition, the analyzed elements of GBI were found to mitigate various global problems, reflecting the SDGs, primarily good health and well-being, sustainable cities, responsible consumption, climate actions, and life on land and in water [53].…”
Section: Elements Of Urban Gbi As Nbsmentioning
confidence: 99%
“…These elements fulfill most of the formal requirements to recognize an intervention as NBS proposed by Sowi ńska-Świerkosz and García [7] (Table 3). Previous research conducted by other authors in relation to different elements of GBI, including UPs [21,37,38], UFs [40][41][42], UWs [42][43][44][45]52], AGs [16,[46][47][48], and Ws [11,49,50], showed that these elements provide and/or improve environmental, social, and economic benefits, such as recreational and spiritual or cultural ecosystem services, physical and mental health, carbon sequestration, air purification, noise reduction, biodiversity and, in the case of AGs and UWs, food provisioning. In addition, the analyzed elements of GBI were found to mitigate various global problems, reflecting the SDGs, primarily good health and well-being, sustainable cities, responsible consumption, climate actions, and life on land and in water [53].…”
Section: Elements Of Urban Gbi As Nbsmentioning
confidence: 99%
“…These evaluations too often consider the UGS to be a homogeneous system. In reality, even without external intervention, the UGS is composed of many living elements (trees, shrubs, herbs, small animals, and users), which change throughout their life; as a consequence, the system also continuously changes, and does so at different speeds depending on its constituent variables [22]. Furthermore, the nature of the internal and external linkages is nonlinear [23] and some of them are, therefore, unpredictable and, to a certain extent, unknown [21].…”
Section: Urban Greenery As a Complex Systemmentioning
confidence: 99%
“…The same phenomena also lead to the formation of eccentric piths, which can be detected by tree-ring analysis. The vertical stability of a tree can be assessed using an automatic accelerometer (gyroscopic sensor), which measures the position and oscillation in three axes (Matasov et al 2020), therefore, providing useful information on the effect of wind exposure on the tree aerial architecture and species-specific biomechanics.…”
Section: Reaction Woodmentioning
confidence: 99%